Depth-Dependent Correction for Wind-Driven Drift Current in Particle Tracking Applications - van der Mheen, Mirjam; Pattiaratchi, Charitha; Cosoli, Simone; Wandres, Moritz (Frontiers in Marine Science, 2020)
Predicting the trajectories of buoyant objects drifting at the ocean surface is important for a variety of different applications. To minimise errors in predicted trajectories, the dominant transport mechanisms have to be considered. In addition to the background surface currents (i.e. geostrophic, tidal, baroclinic currents), the wind-driven drift current can have a significant influence on the dynamics of buoyant objects. The drift current consists of two components: Stokes drift and a wind-induced shear current. The drift current has a strong vertical profile that can have a large influence on the transport of buoyant objects. However, few practical methods exist that consider the vertical profile of the drift current when predicting particle pathways on the ocean surface. The aim of this paper is to introduce a depth-dependent drift current correction factor (``drift factor''). We test the usefulness of this drift factor by simulating the transport of two types of ocean surface drifters, released simultaneously within the coverage of a high-frequency ocean radar (HFR) system. Our results show velocity differences between the two types of drifters and the HFR measured ocean surface currents. We suggest that these differences are the result of the drift current vertical profile. Our particle tracking simulations provide an illustrative example, indicating the importance of accounting for a drift factor that takes the variation of the drift current with depth into account.